PENERAPAN PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAM-ACHIEVEMENT DIVISION TERHADAP HASIL BELAJAR MATEMATIKA SD - Nurzaini, Nining (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Â Abstract The purpose of this research is to analize the effect of applying cooperative learning student team-achievement division type to arithmetic sumation and integers subtraction operation for learning outcomes of the IV grade students in SDN 35 Pontianak selatan. The research method thatÂ used is experiment with quasy experiment with nonequivalent control group design. The populasion of this research is the whole of the IV grade students in SDN 35 Pontianak Selatan with total 98 students. The sample of this research are class IV B (control) and class IV C (experiment). The average learning outcomes of post-test class experiment is 82,71 and class control is 71,06 gained is 2,82 and Î± = 5% is 1,6706. So, (2,82) > (1,6706). Then , Ha is accepted. It can be conclude that there is the effect of applying cooperative learning type student team-achievement division to the learning outcome of IV grade students in SDN 35 Pontianak Selatan. Therefore, the effect size is 0,83(high criteria). It means that learning by applying cooperative learning type student team-achievement division to arithmetic sumation and integers subtraction operation gives high effect to the IV grade students in SDN 35 Pontianak Selatan learning outcomes. Â Keywords : Student Team-Achievement Division, Learning Outcomes.